The relationship between technology acceptance and job satisfaction towards staff at Pejabat Pendidikan Daerah, Raub / Syaidatul Alia Dzulkefly - Dzulkefly, Syaidatul Alia (2014)
The research is about the relationship between job satisfaction and technology acceptance towards staff. Technology acceptance mode explains the factor that affect behavioral intentions to use information on computer systems . It as suggest that two key variables which is perceive usefulness and perceive ease of use that determine the intention to use particular system (Davis, 1989). The elements of Technology Acceptance Model, it can measure either employee is perceive usefulness or perceive ease of use to that particular system or application. From that, company can know the level of employee's of satisfaction. Purpose: To determine the relationship of job satisfaction and the independent variable of technology acceptance model (TAM) which are perceive ease of use and perceive usefulness and moderate variable of organizational support such as motivation and training to achieve the job satisfaction. The main objective, to know whether by using perceive usefulness affect the job satisfaction was decrease or increase and vice versa with perceive ease of use. Methods: The staff in Pejabat Pendidikan Daerah, Raub as sample of this research. Thus, used questionnaires as a method to know wether staff in Pejabat Pendidikan Daerah achieve their job satisfaction in the organization or not from technology acceptance model. The data was collected over three weeks which is about 44 people as a sample size at Pejabat Pendidkan Daerah, Raub. Social Science Software (SPSS) versionn 21 was being used to analyzed the research data. Finding: the result showed that, staff in this sample had a moderate level of job satisfaction with the perceive usefulness and perceive ease of use correlated almost equally with job satisfaction. Conclusion: from the analysis i found that the staff at Pejabat Pendidikan Daerah, raub are satisfied with their job wether using technology or not. This is because, they also achieve their job satisfaction by the organizational support such as motivation and training. Recommendation: the others way or solution to increase the job satisfaction towards staff at Pejabat Pendidikan Daerah, Raub by developing leadership skills.